PENGEMBANGAN MODUL BERBASIS BRAIN BASED LEARNING PADA POKOK BAHASAN BARISAN DAN DERET ARITMATIKA TERHADAP PEMAHAMAN KONSEP SISWA: PENGEMBANGAN MODUL BERBASIS BRAIN BASED LEARNING PADA POKOK BAHASAN BARISAN DAN DERET ARITMATIKA TERHADAP PEMAHAMAN KONSEP SISWA - Neno, Dewi Mariana; Yusuf, St. Muthmainnah; Fatmawati, Agustin (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2024)
This study aims to develop a Brain Based Learning – based module on the subject of arithmetic sequences and series onstudents’ conceptual understanding of SMP Negeri 1 Amarasi Timur. This research was conducted at Amarasi Timur 1 Publik Middle School, Odd Semester, 2022/2023 Academic Year. The type of research used is research and development (R&D), namely the development of teaching tools including teaching material modules, test questions, and student response questionnaires. The development method for this device is using a 4D model which includes: (1) the definition stage (Define), (2) the design stage (Design), (3) the development stage (Develop), and (4) the deployment stage (Dessiminate). The subjects in this research trial were class VIII students of SMPN 1 Amarasi Timur and to find out the response of teachers and students to the development of learning modules based on brain based learning. Data analysis techniques in this study were validation tests carried out by media experts and material experts as well as practicality and effectiveness. The results of the study showed that the validation results of Brain Based Learning modules by media experts were 3,58 in the Very Valid category, and results of material experts were 3,50 in the very valid category, overall the average module validation was 3,54 in the very valid category. The feasibility results of the learning module are based on the results of the assessment that the learning module achieves an average total score of 3,06 out of a maximum score of 4% in the practical category. This can be interpreted that media experts state that the learning module is in the valid category an is suitable for use in learning.